Sistem Pemilihan Shichou di Jepang dalam Manga Kunimitsu no Matsuri Karya Yuma Ando dan Masashi Asaki - Sri Widiantari, I Gusti Ayu; Budiana, I Made; Ari Sulatri, Ni Luh Putu (Humanis; Vol 24 No 3 (2020), 2020)
This research is titled “ The Shichou Electoral System in Japan in the Kunimitsu no Matsuri Manga by Yuma Ando and Masashi Asaki”. This research aims to examine the shichou electoral system and election campaign which was held in Japan in the Kunimitsu no Matsuri Manga by Yuma Ando and Masashi Asaki. The method used in this research is a descriptive analysis method by Ratna (2015). The theories used in this research are the s ociological theory of literature proposed by Wellek & Werren (1990), semiotics theory by Hoed (2014) and Ricæ ur ( in Hoed, 2014) , Public Office Election Law Number 100 in 1947. B ased on the result of the analysis found the shichou electoral system is divided into 1) candidate qualifications in shichou election; 2) voter qualifications in shichou election; 3) the procedure for shichou election. Citizens who have qualified to become candidates in the shichou election will do campaign to win the election. The election campaign is divided into 1) implementation of election campaign; 2) ban in election campaign; 3) the media used in the election campaign.